DAMPAK PEMAHAMAN WAJIB PAJAK ATAS PP NOMOR 46 TAHUN 2013 TERHADAP PENERIMAAN PAJAK PENGHASILAN PASAL 21 PADA KPP PRATAMA KOTAMOBAGU - Manengkey, Speny Ria; Pangemanan, Sifrid; Pontoh, Winston (Universitas Sam Ratulangi, 2015)
Tax is a matter that must be well understood by everyone. Because tax hold an important role in the economy of a country. State revenues from taxation were very helpful all existing development. This research is do in KPP Pratama Kotamobagu and on taxpayer in the region Amurang. The variables used in this study were twu variables, namely understanding the taxpayer on the Government Regulation No. 46 of 2013 (X) and income tax revenue article 21 (Y). Data collection method used in this study were questionnaires and interviews. Technical analysis of data using simple linear regression analysis. From simple linear regression test result show that understanding the taxprayer on Government Regulation No. 46 of 2013 had a considerable influence on the acceptance of income tax on KPP Pratama Kotamobagu.